Interaksi Tak Terlihat Menguak Mutualisme, Komensalisme Dan Parasitisme Dalam Kehidupan Tumbuhan - Rafika Sekar Arum; Fresti Ananda Sari (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research explores the invisible interactions that shape plant life, focusing on mutualism, commensalism, and parasitism. Mutualism demonstrates a beneficial relationship, such as mycorrhizal fungi that aid in nutrient absorption for plants. Commensalism, on the other hand, illustrates one party benefiting without harming or benefiting the other party, for example, epiphytic orchids that rely on trees. Finally, parasitism discusses a relationship where one organism benefits at the expense of the host, such as dodder that extracts nutrients from other plants. Understanding these three forms of symbiosis is crucial to uncovering the ecological complexity of plants and their role in maintaining ecosystem balance. This study highlights the vital nature of these hidden interactions for the survival and evolution of plant species.